2013
DOI: 10.1002/2013gc004959
|View full text |Cite
|
Sign up to set email alerts
|

Sea‐ice conditions in the Okhotsk Sea during the last 550 kyr deduced from environmental magnetism

Abstract: [1] Reconstructing past sea-ice conditions in the Okhotsk Sea is important because sea-ice conditions vary in response to global climate changes, which in turn may affect global ocean circulation through intermediate water mass formation. We conducted an environmental magnetic study of six cores from three stations in the central Okhotsk Sea to better understand temporal and spatial sea-ice variations. Intercore correlations and age estimations are based mainly on geomagnetic paleointensity; an oxygenisotope s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Natural remanent magnetization (NRM) measurements with stepwise alternating field (AF) demagnetization were performed using a cryogenic magnetometer system with an in-line static AF demagnetizer (2G Enterprises model 760, Applied Physics Systems, Inc., Mountain View, CA, USA) in a magnetically shielded room of GSJ, AIST. Generally, the maximum angular deviation (Kirschvink 1980) values were less than 5°, which indicates that stable primary magnetization was preserved (Inoue and Yamazaki 2010;Yamazaki et al 2013). The mean paleomagnetic inclinations of the cores are close to those expected from the geocentric axial dipole model for the respective site latitudes.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Natural remanent magnetization (NRM) measurements with stepwise alternating field (AF) demagnetization were performed using a cryogenic magnetometer system with an in-line static AF demagnetizer (2G Enterprises model 760, Applied Physics Systems, Inc., Mountain View, CA, USA) in a magnetically shielded room of GSJ, AIST. Generally, the maximum angular deviation (Kirschvink 1980) values were less than 5°, which indicates that stable primary magnetization was preserved (Inoue and Yamazaki 2010;Yamazaki et al 2013). The mean paleomagnetic inclinations of the cores are close to those expected from the geocentric axial dipole model for the respective site latitudes.…”
Section: Methodssupporting
confidence: 68%
“…All cores contain a few thin volcanic ash layers and some detrital components. The results of a paleomagnetic and rock magnetic study of these cores were reported in Inoue and Yamazaki (2010) and Yamazaki et al (2013). The ages of the bottom of the gravity cores range from approximately 120 to 160 ka.…”
Section: Materials and Samplingmentioning
confidence: 99%
“…Relative paleointensity and magnetic properties of the three major sites, GC1 + PC7, GC8 + PC6, and GC9 + PC5, were already reported by Inoue and Yamazaki (2010) and Yamazaki et al (2013). The procedure of paleo-and rock magnetic measurements of other gravity-core sites, GC3, GC5, GC6, GC10, GC11, and GC12, was the same as that of Inoue and Yamazaki (2010) and Yamazaki et al (2013). Stepwise alternatingfield (AF) demagnetization showed univectorial behavior in general except for a soft secondary component that was removed at AF of 10 mT or less.…”
Section: Samples and Methodssupporting
confidence: 58%
“…Discrete samples for paleo-and rock magnetic measurements were taken sequentially from the half-split core surfaces using plastic cubes of 7 cm 3 each. Relative paleointensity and magnetic properties of the three major sites, GC1 + PC7, GC8 + PC6, and GC9 + PC5, were already reported by Inoue and Yamazaki (2010) and Yamazaki et al (2013). The procedure of paleo-and rock magnetic measurements of other gravity-core sites, GC3, GC5, GC6, GC10, GC11, and GC12, was the same as that of Inoue and Yamazaki (2010) and Yamazaki et al (2013).…”
Section: Samples and Methodsmentioning
confidence: 62%
See 1 more Smart Citation